EFEKTIFITAS HYPNO-EFT DAN PERNAFASAN YOGA DALAM MENURUNKAN KECEMASAN IBU HAMIL DI BPM NY. SRI KUSTINAH - Salafas, Eti; Anisa, Rifka; Rusita, Vivi Ida (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
Anxiety third trimester pregnant women in the face of labor one of the problems frequently encountered emotional disturbance and psychological impact is serious enough. Hypno EFT and breathing yoga is an attempt to reduce the anxiety. This study aims to determine the effectiveness of hypno EFT and yoga breathing to changes in anxiety levels of pregnant women in the third trimester in BPM Ny. Sri Kustinah Semarang. This type of research was "Quasi experiment" used twogroup pretest - posttest design. Samples were third trimester pregnant women in BPM Ny. Sri Kustinah amounted to 20 respondents were divided into 2 groups with purposive sampling technique. Data processing technique used paired sample t-test. The results showed that the average value of changes in anxiety using yoga breathing (12.696) is greater than hypno EFT (9.279). The conclusion of this study is more effective yoga breathing to changes in anxiety third trimester pregnant women compared with hypno EFT. Keywords: Hypno EFT, Breathing Yoga, Anxiety Tthird Trimester Pregnant women